Electronic Criminal Justice in Indonesia: Challenges and the Future Measures - Barlian, Aristo Evandy A.; Latipulhayat, Atip; Rusmiati, Elis; Wulandari, Widati; Sukma, Ahmad Novindri Aji (Universitas Negeri Gorontalo, 2025)
Electronic trials represent a radical innovation within the judicial system, viewed as a means to simplify and facilitate access to justice for those seeking it. However, electronic criminal trials continue to present both legal and technical challenges. This writing aims to explore the development of electronic criminal trials in Indonesia and compare them with several other countries. It also outlines the issues and challenges involved, while proposing future measures to ensure electronic trials function as intended. The approach used in this paper is based on statutory and comparative methods. The findings indicate that radical innovations, particularly in electronic trials, highlight the need for sustainability, but also reveal legal and technical challenges. The legal aspect concerns the level of regulation within the Supreme Court Regulations, which ideally should be elevated to the level of the Criminal Procedure Code. There is also ambiguity regarding the criteria for implementing electronic criminal trials. Compared to the United States, where clear criteria are established, Indonesia lacks such clarity. On the technical aspect, challenges such as unequal access to the internet, network disparities, and limited human resources need to be addressed. For the future success of electronic criminal trials, it is necessary to establish clear regulations at the level of the Criminal Procedure Code; provide equal network access to ensure electronic trials can be conducted in all courts across Indonesia; improve the quality of electronic trial services, especially for vulnerable groups (such as the elderly and people with disabilities); and enhance data security systems to protect personal information, as demonstrated by Kyrgyzstan.